2021
DOI: 10.1109/access.2021.3090445
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Generate Steganographic Cover for Audio Steganography Using GAN

Abstract: Audio steganography aims to exploit the human auditory redundancy to embed the secret message into cover audio, without raising suspicion when hearing it. However, recent studies have shown that the existing audio steganography can be easily exposed with the deep learning based steganalyzers by extracting high-dimensional features of stego audio for classification. The existing audio steganography schemes still have room for improvements. In this work, we propose an audio steganography framework that could aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The image steganography is divided into three parts, namely (1) least significant bits coding, (2) masking and filtering, and (3) transformations. Audio steganography Audio steganography is a technique that is used to transmit secret data by modifying a digitalized audio signal in an imperceptible manner [ 129 ]. Following types of audio steganography are given: (1) least significant bits coding, (2) phase coding, (3) spread spectrum, and (4) echo hiding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The image steganography is divided into three parts, namely (1) least significant bits coding, (2) masking and filtering, and (3) transformations. Audio steganography Audio steganography is a technique that is used to transmit secret data by modifying a digitalized audio signal in an imperceptible manner [ 129 ]. Following types of audio steganography are given: (1) least significant bits coding, (2) phase coding, (3) spread spectrum, and (4) echo hiding.…”
Section: Resultsmentioning
confidence: 99%
“…Audio steganography is a technique that is used to transmit secret data by modifying a digitalized audio signal in an imperceptible manner [ 129 ]. Following types of audio steganography are given: (1) least significant bits coding, (2) phase coding, (3) spread spectrum, and (4) echo hiding.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of [ 31 ] suggested technology for audio steganography that could lead to superior steganographic cover audio for automatic message embedding. The proposed framework’s training architecture consisted of three components: a generator, a discriminator, and a taught steganalyser, based on deep learning.…”
Section: Section 2: Related Workmentioning
confidence: 99%
“…Penelitian selanjutnya [24] mengungkapkan bahwa teknik penyembunyian pesan pada gambar atau steganografi gambar dapat dideteksi oleh teknik steganalisis, sehingga keamanan pada pesan yang disembunyikan terancam. Selanjutnya penelitian [25] menerapkan algoritma GAN pada steganografi gambar sebagai metode yang bertujuan untuk mengacak atau memanipulasi pesan yang ada pada data digital berupa audio sehingga tidak mudah dideteksi oleh teknik steganalisis.…”
Section: Pendahuluanunclassified